The impact of climate risk on renewable energy investments - Li, Xiaoshu; Zheng, Zhuo; Li, Haixia (Frontiers in Environmental Science, 2025)
To address the issues of climate change, many countries are taking transitions from traditional fossil energy to renewable energy. The renewable energy enterprises are more sensitive to the impacts of policy uncertainty and weather conditions compared to other types of investment. This study employs data from 179 A-share listed renewable energy enterprises in 2008–2022 to explore the impacts of different types of climate risk on the investments of renewable energy industry. The results show that transition risk has a positive effect on the investment of renewable energy enterprises, especially when the level of economic development is below the threshold. In the panel threshold model, extreme high temperature and extreme precipitation would promote the investments of state-owned renewable energy enterprises. When renewable energy enterprises are under high financing constraints, only transition risk can promote the investments.